PERAN PENGELOLA PERSATUAN ORANG TUA MURID DAN GURU PPT BUNGA TERATAI PADA PENURUNAN STUNTING MELALUI GERAKAN SADAR GIZI SEIMBANG - Azminah, Suhartini Nurul; Oktaviani, Rizki Nur; Zuroida, Aironi (UNIVERSITAS PGRI MADIUN, 2025)
Abstract. The purpose of this community service is to handle stunting in PPT Bunga Teratai students through the role of managers, both the principal, the Parent and Teacher Association (POMG) by implementing the